Melatonin protects chicken follicular granulosa cells against oxidative damage-induced apoptosis via inhibiting FOXO1 signaling pathway - Xuelu Liu; Keqian Di; Xiangyu Chen; Chenxuan Huang; Fei Hou; Jianku Hou; Erying Hao; Kang Bai; Dehe Wang; Lei Shi; Yifan Chen; Hui Chen (Poultry Science, 2025)
In laying hens, the age-related decline in egg production efficiency is largely attributed to ovarian dysfunction and increased follicular atresia, which are aggravated by oxidative damage mediated by reactive oxygen species (ROS). Melatonin (Mel) demonstrates powerful antioxidant capabilities, which are essential in eliminating free radicals and enhancing antioxidant enzymes, crucial for the development of follicles. Forkhead Box Protein O1 (FOXO1), a key member of the FOXO family, plays a vital role in regulating various physiological processes involved in follicle growth, maturation, and atresia. This study focused on examining the impact of Mel on chicken follicular granulosa cells (CFGCs) upon oxidative stress and investigated its specific mechanisms. An oxidative stress model was developed using exposure to hydrogen peroxide (H₂O₂) at a concentration of 50 μmol/L for 6 h. This model was based on dose-response curves analyzing cell viability, ROS fluorescence intensity, contents of malondialdehyde (MDA), and antioxidant enzyme activities (SOD). Subsequently, we explored the effects of Mel on CFGCs under conditions of oxidative stress, discovering that Mel mitigated the oxidative damage and cellular apoptosis triggered by H2O2. This protective effect was achieved by significantly reducing (P < 0.05) ROS production and modulating the expression of key genes and proteins. It led to upregulation of catalase (CAT), superoxide dismutase isoforms 1 and 2 (SOD1, SOD2), glutathione peroxidase 3 (GPX3), peroxiredoxin 3 (PRDX3), and B-cell lymphoma 2 (BCL-2), but downregulated BCL-2-interacting mediator of cell death (BIM), Caspase-3, and BCL-2-associated X protein (BAX) upon H2O2 exposure (P < 0.05). Additionally, the expression levels of FOXO1, a critical gene and protein in the Mel-treated group, were significantly reduced (P < 0.05), indicating that Mel may safeguard ovarian cells from oxidative damage by suppressing the FOXO1 signaling pathway. To further examine this, we developed models using siRNA against FOXO1 (si-FOXO1) and overexpressing FOXO1 (pcDNA3.1-FOXO1). The results indicated that exposure to Mel significantly increased (P < 0.05) BCL-2 levels while decreasing FOXO1, BIM, Caspase-3, and BAX expressions in both si-FOXO1 and pcDNA3.1-FOXO1 models. Ultimately, these findings suggest that Mel protects CFGCs against oxidative damage-induced apoptosis through inhibiting FOXO1 signaling pathway.